Improving English Teachers' Ability in Analyzing Students' Learning Needs for Cross-Curriculum Project-Based Learning Planning - Nugraha, Irsyad; Tawanggono, Ghandy Ardyan; Damayanti, Hemalia; Admajayanti, Fifian; Salsabila, Dya; Kartika6, Hilda Sry; Suparman, Asep (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service program aims to enhance the ability of English teachers in analyzing students’ learning needs for planning cross-curricular project-based learning. The program was carried out through observation, workshops, practice, mentoring, and evaluation stages. Teachers were trained in developing instruments for learning needs analysis and designing project-based lesson plans. The implementation showed that teachers gained a better understanding of student needs and improved their ability to design contextual, interactive, and collaborative learning activities. Furthermore, the training strengthened teachers’ confidence in applying project-based learning aligned with the Merdeka Curriculum. The outcomes indicated that continuous training and institutional support are essential to sustain teacher professional development and to improve the quality of English language teaching in schools.